Science curricula design: analysis of authors’ ideological and pedagogical principles - Ferreira, Sílvia (2022)
The study analyses the extent to which the sociological message transmitted by the Official Pedagogic Discourse of the curriculum for Portuguese middle schools contains the ideological and pedagogical principles of its authors. The research is epistemologically and sociologically grounded, placing particular emphasis on Bernstein theory of pedagogic discourse. The ideological principles underlie broad educational aims and the pedagogical principles underlie characteristics of the pedagogic practice. Data was obtained through a semi-structured interview with the authors and documental analysis of their publications. The results suggest that the authors were distinct in the ideological and pedagogical principles they valued and that discontinuities were evident between those principles and the curriculum message. These results are discussed and their consequences in terms of scientific learning are explored.